EFEKTIVITAS PEMBELAJARAN DARING DI MASA PANDEMI COVID 19 BAGI MAHASISWA STKIP AHLUSSUNNAH BUKITTINGGI - Nisye Frisca Andini (STKIP Pesisir Selatan, 2021)
The difficulty of handling the corona virus has made many state leaders determine steps to stop its spread, even having to determine very difficult policies, one of the policies that greatly affects various aspects of life is the limitation of social interaction, this restriction will certainly affect especially in the field of education, because for the sake of stop the spread of this corona all students and lecturers study from home, a change in the way of teaching and learning from face-to-face or offline (outside the network) to online (in the network) requires the readiness of all elements, the purpose of this study is to find out how much effectiveness online learning is during the covid 19 pandemic for STKIP Ahlussunnah Bukittinggi students. This study uses a quantitative model with a survey method. Respondents from this study amounted to 126 students. The results of this study indicate that 89% of students want face-to-face learning, while only 9% of students want online learning, while 2% want online forever, it can be concluded that online learning is seen from the effectiveness, online learning has not been able to achieve learning objectives. The unpreparedness of students and lecturers, both in terms of the ability to use technology and the availability of adequate learning facilities, poor internet network connections at home, costs, and the inability of students and lecturers to adapt to new learning methods to be able to provide virtual conducive classroom conditions. factors that make online learning has not been effectively implemented.